M&E design deliverable under the contract BRACU-DS-BUCG-2019-001 as of Dec 12, 2020 - BUCG (Brac University, 2023)
This record consists of general correspondence regarding the M&E designs that are deliverable under the contract BRACU-DS-BUCG-2019-001 as of Dec 12, 2020 for BRACU new campus project.